Pedagogia surda: o papel de professoras surdas na construção de identidade de alunas surdas e alunos surdos - Silva, Lucas Romário da (2017)
This research aims to investigate the role of Deaf teachers in the construction of identities of Deaf students, based on their discourses and pedagogical practices. Anchored in the field of Cultural Studies and Deaf Studies, we seek to understand the different scenarios that surround Deaf people in the educational process, especially the cultural relations among Deaf people, specifically between Deaf teachers and Deaf students. We assumed that the educational processes are more effective in the presence of female and/or male Deaf teachers, who value Deaf Culture in a direct relationship with Deaf people. Thus, this master’s thesis deals with pedagogical-cultural relations within the Specialized Educational Service (SES) involving three female Deaf teachers and their Deaf students, in common schools of João Pessoa-PB. The research was based by the qualitative approach, using semi-structured interviews and non-participant observation. Empirical evidence reveals that, in their relationship with Deaf teachers, Deaf students tend to develop cultural strategies that allow them to build the foundations of Deaf identities, even in the context of standardizing cultural practices. This happened because the teachers provided their students with cultural, historical and political knowledge about their cultural group, highlighting processes of identification with their similarities as Deaf people. The pedagogical situations indicated that, in their relationship with Deaf teachers, Deaf students had the opportunity to understand their place in the world, and that they were not handicapped and incapable persons, but different people who possessed a unique culture represented by a visual experience and the sign language. As a battle flag of Deaf teachers in schools, this language represents one of the main contributions of their role in the educational processes of Deaf students, since it is through it that the identity construction – in its multiplicity – becomes possible. Therefore, we conclude that Deaf teachers have fundamental role in the process of identity construction of Deaf students, not only for highlighting the Deaf culture and differences, but also for transcending them, teaching school contents, exchanging life experiences and even sharing the anguish experienced only by Deaf people.